Pengaruh Menulis Ekspresif dalam Menurunkan Stres pada Wanita Penderita Penyakit Lupus - Andi Hadratul Ainiyu; Sitti Murdiana; Ahmad Ridfah (Universitas Kristen Maranatha, 2020)
The stress experienced by women with lupus will be able to make their illness worse and by writing expressively lupus sufferers can bring out stressful thoughts and feelings, so that stress levels can decrease. The purpose of this study was to determine the effect of expressive writing in reducing stress in women with lupus. The subjects of this study were patients with lupus who were undergoing outpatient treatment at Wahidin Sudirohusodo Hospital, totaling two people who were female (N = 2). The instrument used is the DASS-S scale from Lovibond and Lovibond, which is translated by Damanik. Analysis of the data used compares the pre-test and post-test average results and uses visual inspection. The results of this study indicate that expressive writing can reduce stress in women with lupus. This research is expected to be one of the suggestions for reducing stress in women with lupus. Keywords: expressive writing, stress, and women with lupus